Estudo do comportamento da contaminação dos aços em distribuidores de lingotamento contínuo por meio de modelos dinâmicos - Simão Vervloet Ramos (2022)
The continuous casting tundish has a fundamental role in the quality of the steel. In addition to removing part of the non-metallic inclusions from secondary refining, the tundish has the aim to ensure a contamination-free path from the ladle to the molds. Nowadays, in which high levels of steel cleanliness are obtained in ladle treatments, the study of contamination factors in the tundish gains more relevance. For this purpose, the use of dynamic models developed in the software of computational thermodynamics is adequate, because they have proven accuracy when compared to the industrial data. Therefore, in this thesis, dynamic models were elaborated for the study of steel contamination in the tundish by atmospheric gases, with a focus on the transient periods of operation (filling and ladle change). The models were developed based on of the effective equilibrium reaction zone, using also coupled heat transfer and phase change routines. The flow patterns were evaluated and modeled from compartment models. Furthermore, the contaminations concerning the use of SiO2-rich cover powder and the practice of plasma heating were also addressed. In general, the contamination in the tundish has a cumulative trend in the filling stage and a dissolution trend in the casting stage. The SiO2-rich cover powder promotes the continuous contamination of the steel, and the layer undergoes considerable chemical deterioration, being enriched with other oxides such as Al2O3 and MnO. The porosity of the cover powder layer has a great influence on the heat loss of the metallic bath and the contamination level by the end of the first heat of a casting sequential. The use of plasma heating practice also boosts a soaring contamination level by the end of the first heat, in which may achieve higher levels than those of the filling stage. Analyses of the influence of operation parameters and different levels of start-up inertization show the incorporation trends of gases and can serve as a reference to mitigating the contamination in transient periods of operation. For calcium-treated aluminum-killed steels, the non-metallic inclusions from the ladle undergo severe modification of chemical composition even with low levels of steel reoxidation, only returning to the original composition after a long period of casting.